Scanning Signatures: A Graph Theoretical Model to Represent Visual Scanning Processes and A Proof of Concept Study in Biology Education - Enrique Garcia Moreno-Esteva; Anttoni Kervinen; Markku S. Hannula; Anna Uitto (MDPI AG, 2020)
In this article we discuss, as a proof of concept, how a network model can be used to analyse gaze tracking data coming from a preliminary experiment carried out in a biodiversity education research project. We discuss the network model, a simple directed graph, used to represent the gaze tracking data in a way that is meaningful for the study of students' biodiversity observations. Our network model can be thought of as a scanning signature of how a subject visually scans a scene. We provide a couple of examples of how it can be used to investigate the personal identification processes of a biologist and non-biologist when they are carrying out a task concerning the observation of species-specific characteristics of two bird species in the context of biology education research. We suggest that a scanning signature can be effectively used to compare the competencies of different persons and groups of people when they are making observations on specific areas of interests.